Registration of 'NS Presser CLP' Hard Red Spring Wheat. Issue 1 (7th September 2017) - Heo, H.-Y.; Blake, N. K.; Lanning, S. P.; Lamb, P. F.; Nash, D.; Wichman, D. M.; Kephart, K. D.; Stougaard, R. N.; Miller, J. H.; Reddy, G. V. P.; Eckhoff, J. L.; Chen, C.; et al.
Abstract : 'NS Presser CLP' (Reg. No. CV‐1132, PI 679964) hard red spring wheat ( Triticum aestivum L.) was developed by the Montana Agricultural Experiment Station and released in 2016 to the commercial partner Northern Seed LLC. NS Presser CLP is a two‐gene Clearfield wheat intended for use with the selective imidazolinone herbicide imazamox (Beyond, BASF Corp.). NS Presser CLP was developed by a single backcross of alleles for resistance to the imidazolinone herbicide class into the recurrent parent 'Vida'. Vida has been the most widely grown hard red spring wheat cultivar in Montana since 2010. Alleles for herbicide resistance at TaAHAS1D and TaAHAS1B were selected during the backcrossing process and line derivation using polymerase chain reaction markers developed by BASF. Three years of replicated yield trials at a total of 23 sites showed that NS Presser CLP has yield potential under dryland production similar to Vida. NS Presser CLP showed tolerance to a 2× rate of imidazolinone herbicide (87.6 g a.i. ha −1 ) applied at three testing sites in each of 2 yr. It provides a high‐yielding Clearfield cultivar for dryland production in Montana and surrounding areas.